Bilateral asymmetries in male and female young elite fencers in relation to fencing performance - Drakoulaki, V.; Kontochristopoulos, N.; Methenitis, S.; Simeonidis, T.; Cherouveim, E.; Koulouvaris, P.; Savvidou, O.; Tsolakis, C. (Isokinetics and Exercise Science, 2021)
BACKGROUND: Data about lower extremities` strength and power asymmetries in fencers, and their relationships to fencing performance are limited and inconsistent. OBJECTIVE: The aim of the present study was to investigate asymmetries, between dominant (D) and non-dom (ND) legs of elite young male and female fencers, in relation to performance in fencing specific tests. METHODS: Anthropometric characteristics, unilateral vertical-horizontal jumping, isokinetic strength, lunge and step lunge performances were evaluated in 16 male and 22 female elite fencers. RESULTS: Significant differences between genders were found for all anthropometric measurements (p< 0.05). No significant bilateral asymmetries and gender x laterality effects were observed (p> 0.05). Fencing performance was negatively correlated with the D leg`s flexion/extension (F/E) ratio at 300°/s (r: -0.564 to -0.619, p< 0.05). In addition, D leg`s F/E ratio at 300°/s was positively related to lung peak velocity and power in female fencers (r: 0.562-0.649; p< 0.05). Finally, only in female fencers, unilateral triple hop distance was significantly related to lung peak velocity and power (r: 0.442-0.500; p< 0.05). CONCLUSIONS: The results of the present study suggest that the differential activation/movement pattern of the D and ND leg muscles do not lead to anatomical, dynamic and functional lower extremities asymmetries.